Competências em informação: Um fator crítico para a comunicação na atualidade - Cól, Ana Flávia Sípoli [UNESP]; Belluzzo, Regina Célia Baptista [UNESP] (My University, 2011)
Information is one of the most essential raw materials of the journalist. Therefore, for a positive professional development in all means of communication, one must use it with quality. Thus, the development of information proficiency can help with the execution of the job in a more efficient and responsible manner. All of which is indispensable facing the importance of the journalistic discourse as a mediator nowadays, as well as the challenges that the journalist faces with the advent of new information and communication technologies.
Information proficiency: A critical factor for communication nowadays
Keywords: Information proficiency; Journalism; Responsibility to inform; Social roles